Comparative in vitro evaluation of cefpimizole (U-63196E), a new antipseudomonal cephalosporin. - LeFrock, J L (1985)
The activity of cefpimizole (formerly U-63196E) was compared with that of other broad-spectrum cephalosporins and penicillins. Overall, cefpimizole exhibited limited activity against gram-positive cocci and members of the family Enterobacteriaceae as compared with the other cephalosporins tested. The activity of cefpimizole against Pseudomonas aeruginosa was similar to that of cefoperazone and mezlocillin (90% MIC, 32 micrograms/ml) but poorer than that of ceftazidime (90% MIC, 8 micrograms/ml). Cefpimizole appears to have no in vitro advantage over the cephalosporins with which it was compared.